IoT-based Smart Piggy Bank Design Implementation Using RFID and Telegram Notification - Komarudin, Rizal Maulana; Suteddy, Wirmanto; Agustini, Devi Aprianti Rimadhani (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
Saving is one of the most important things in financial management. Saving is beneficial for the long term for life. In the conventional way, people can save in a closed container or generally use an object called a piggy bank. However, there are still many shortcomings of the current conventional piggy bank, such as having to be disassembled to take the money and it is difficult to monitor the amount of savings in it so that it can only be used once. With the help of technology, these conventional tools can be used better and more efficiently. This smart piggy bank can be integrated with the Telegram when money is inserted so that it becomes more monitored in saving. The money inserted is detected by infrared sensors and color sensors which are then accumulated and sent via Telegram. Previously, there has been similar research in using sensors to detect money and send notifications based on the Internet of Things. This research aims to develop the existing research by integrating some of its features. Testing was conducted using the Black Box method, focusing on the functionality of the device. As a result, the money inserted into the piggy bank can be accumulated properly and monitored via Telegram with a calculation according to the amount of money inserted and can be used by many people because it uses an RFID card that contains user data and savings so that it becomes more efficient and recorded.